Speech development of early children: features of training special teachers (Journal of Educational Sciences, 2024)
The article examines the problem of speech development in young children, studied by scientists in this field from different countries. The problem of the readiness of domestic special teachers to conduct speech therapy work with young children is also described. Particular attention is paid to the issue of preparing special teachers for speech therapy support for young children in preschool general education organizations. Based on the analysis of research and data obtained as a result of a survey of specialists, a conclusion was made about the importance of studying the problems of speech development of young children and targeted training of special teachers to work with this category of children, as the main approach to solving the issues of overcoming speech delays and preventing the occurrence of secondary disorders.Representatives of preschool educational organizations took part in the survey: heads, methodologists, educators and special teachers. The interviews were conducted in general education kindergartens in Almaty, Kostanay, Pavlodar, Karaganda and Shymkent.The information presented in the article can be used by practitioners to replenish theoretical knowledge, as well as by researchers studying issues of speech development in young children.Keywords: early age, speech development, training of special teachers, speech therapy support.